Language shift in a majority ethnolinguistic speech community :a case study of a foochow chinese family in Sibu - Hung, Yu Ling. (Universiti Malaysia Sarawak, UNIMAS, 2007)
This case study examined the extent of language shift across generations within a Foochow Chinese family in Sibu, a Foochow-dominant town in the Malaysian state of Sarawak. In specific, this study investigated language choice patterns within and across generations in the family domain, the speakers’ self-rated Foochow dialect proficiency, the reasons of the speakers’ language choice, and the key factors of language shift . This case study offered insight into the actual language situation of a majority Chinese ethnic group, based on interview data from 30 participants in an extended Foochow Chinese family. In the context of Sibu, Foochow Chinese is the largest group within the Chinese community. One would say that there is no possibility of language shift because of the majority Foochow Chinese and the prevalence of Foochow dialect in Sibu town. Nevertheless, the results of the current study showed that there was strong evidence of intergenerational language shift away from the ethnic language to the standard language in this community. This intergenerational language shift was accompanied by the decrease of Foochow dialect proficiency among the younger generations. The result also revealed that the intergenerational shift was because of institutional and socio- cultural factors in which government policy was the most influential factor that caused the shift.